EFEKTIFITAS MUSIK RELIGI TERHADAP PENURUNAN NYERI PASCA BEDAH PADA PASIEN TURP - Mudzakkir, Muhammad (Universitas Pesantren Tinggi Darul Ulum, 2025)
The post TURP surgery wound is found causing pain and bladder spasm. This research is designed to identity the effectiveness of religious music in reducing post TURP surgery pain, by using quasi experiment design with pre and post test control group design. Thirty four samples were recruited using consecutive sampling method, and then divided into 2 groups: the intervention group (analgesic and religious music therapy combination), and control group (analgesic therapy). The data analysis result discovered that religious music therapy was significant in reducing the pain level with p value=0,000. According to this finding, it is recommended for hospitals to integrate religious music therapy in managing post surgery pain. Keywords: post TURP, pain, religious music therapy